2014
DOI: 10.1021/am501041t
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement in Ion Adsorption Rate and Desalination Efficiency in a Capacitive Deionization Cell through Improved Electric Field Distribution Using Electrodes Composed of Activated Carbon Cloth Coated with Zinc Oxide Nanorods

Abstract: Electrodes composed of activated carbon cloth (ACC) coated with zinc oxide (ZnO) nanorods are compared with plain ACC electrodes, with respect to their desalination efficiency of a 17 mM NaCl solution at different applied potentials. Polarization of the ZnO nanorods increased the penetration depth and strength of the electric field between the electrodes, leading to an increase in the capacitance and charge efficiency at reduced input charge ratios. Uniform distribution of the electric field lines between two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 40 publications
1
31
0
1
Order By: Relevance
“…Upon increasing the scan rate to 50 mV/s, capacitance reduced to 40 F/g (Fig. 1b), attributed to reduced time available for ion adsorption along with a denser mass transfer at the electrode-electrolyte interface leading to overlapping double layers at pore entrances [11,15]. The large capacitance values correspond well with the porous structure of ACC, giving it an active specific surface area (SSA) of~1000 m 2 /g (as measured from NMR experiments), which is comparable to SSA of activated carbon powders and other traditionally used electrode materials [18,43,44].…”
Section: Electrode Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Upon increasing the scan rate to 50 mV/s, capacitance reduced to 40 F/g (Fig. 1b), attributed to reduced time available for ion adsorption along with a denser mass transfer at the electrode-electrolyte interface leading to overlapping double layers at pore entrances [11,15]. The large capacitance values correspond well with the porous structure of ACC, giving it an active specific surface area (SSA) of~1000 m 2 /g (as measured from NMR experiments), which is comparable to SSA of activated carbon powders and other traditionally used electrode materials [18,43,44].…”
Section: Electrode Characterizationmentioning
confidence: 99%
“…4b). At a given rate of change of potential, a reduction in the peak inrush current indicates a reduced capacitance [15], attributed to clogging of the electrode pores by organic contaminants in well water leading to a reduction in the total salt adsorption capacity. On a positive note, the lower current led to a reduction in the power consumption per m 3 of desalted water from 0.85 kWh for synthetic water to 0.78 kWh for well water (Table 1).…”
Section: Samplementioning
confidence: 99%
See 1 more Smart Citation
“…Water to be desalinated passes between or across the electrodes [6] and is desalted by the potential mediated adsorption of ions onto the electrode surfaces [9][10][11][12][13][14][15]. Prior research has shown that the capacity of adsorbed ions and their adsorption rate is linked to the strength and distribution of localized electric field produced at the electrode surfaces [7,10,[16][17][18], which in turn is governed by the electrical properties of the electrode [10,16,19]. Given the difficulty in standardizing the electrode properties which are synthesis/fabrication process dependent, there will always be an inherent in-homogeneity between the anode and cathode surface properties of a CDI cell.…”
Section: Introductionmentioning
confidence: 99%
“…Alternative designs use carbon electrode wires [80], flowable electrode slurries [7,[72][73][74]76] or flow-through electrodes [112]. In addition, electrodes can be chemically modified [88,113], nanoparticles can be incorporated [114][115][116], ion-selective coatings can be applied [117,118], or ionexchange membranes can be placed in front of the electrodes in a modification called Membrane Capacitive Deionization, or MCDI [27,28,35,71,102,[119][120][121].…”
Section: Introductionmentioning
confidence: 99%